DDIS-36. BTP-7, A NOVEL PEPTIDE FOR THERAPEUTIC TARGETING OF MALIGNANT BRAIN TUMORS. (11th November 2019) - von Spreckelsen, Niklas; Ghotmi, Yarah; Fadzen, Colin; Wolfe, Justin; Hartrampf, Nina; Bergmann, Sonja; Qu, Yuan; Murrell, Emily; Bononi, Fernanda; Luyt, Leonard; Lamfers, Martine; Ligon, Keith; et al.
Abstract: High-grade gliomas are deadly cancers, and current standard-of-care has demonstrated limited success. The ability to specifically target glioma cells allows for the development of safer and more efficacious brain cancer therapy strategies. Brevican, a CNS-specific extracellular matrix protein is upregulated in glioma cells and its expression correlates with tumor progression. Particularly, a brevican isoform lacking glycosylation, B/bΔg is a unique glioma marker and not expressed in non-cancerous tissues. Therefore, B/bΔg represents a valuable target for anti-cancer strategies. Here, we describe the utilization of state-of-the-art platforms to screen a one-bead-one-compound combinatorial peptide library to discover a novel "B/bΔg-Targeting Peptides", called BTP-7 that can bind B/bΔg with high affinity and specificity. BTP-7 displayed 260 nanomolar affinity for recombinant B/bΔg protein. Binding to a specific site on B/bΔg was confirmed in a competitive binding assay using BTP-7 functionalized with a UV-crosslinker and BTP-7 had little association with the fully glycosylated isoform of brevican (control). Scrambling of the BTP-7 sequence led to complete abrogation of B/bΔg binding. Furthermore, BTP-7 is preferentially taken up by B/bΔg-expressing glioma cells compared with non-expressing cells. We also discovered that BTP-7 can cross the blood-brain barrier in both the in vitro BBB organoid model and in mice. BTP-7 displayed 10x greater binding to intracranial GBM-6 tumors than control peptides, and 4x higher tumor uptake than in normal brain tissues. Conjugation of BTP-7 to camptothecin (an anti-tumor drug) via a cleavable linker led to increased DNA damage in intracranial GBM-6 tumors and prolonged survival in tumor-bearing mice. Our results show the potential of BTP-7 for the development of next-generation targeted therapeutics that could greatly benefit the outcome of patients with advanced brain cancer.